Nutrient deficiency symptomology in citrus: An effective diagnostic tool or just an aid for post –mortem analysis - K. Srivastava, A. (Agricultural Advances, 2013)
Nutrient responsiveness of citrus is evaluated through nutrient diagnostics based on leaf analysis, soil analysis, juice analysis, enzyme function and deficiency symptoms. Of them, deficiency symptoms are most widely used, although with a minimum practical implications on the orchard performance. Development of visible symptoms is attributed to metabolic disorders, causing changes in micromorphology before such symptoms are identifiable. The way in which symptoms develop and manifest themselves on different plant parts gives a reliable indication of the cause of nutritional disorders. But relying solely on deficiency symptoms will be too late for timely diagnosis of nutrient constraints unless complemented with both leaf and soil analysis data. Deficiency symptoms are more like doing post-mortem of decline in orchard performance than timely diagnosing the genesis of nutrient deficiency.